Participatory simulation framework to support learning computer science. (18th October 2007) - Yin, Chengjiu; Ogata, Hiroaki; Yano, Yoneo
This paper proposes a participatory simulation framework using the fundamental concepts in scaffolding and fading to support computer science learning called Learning Computer Science using Participatory Simulation (LCSPS). As an implementation, this framework is the basic for creating the Algorithms for Optimisation and Simulation (ALGOS) (PDA-based Learning Algorithms System) system to support learning sorting algorithm. Using ALGOS, the teacher can assign tasks to learners and ask them to do the task. Learners receive these tasks, collaborate together and exchange their physical positions according to the task assigned. The main purpose of ALGOS is to help the learners to deeply understand the feature of the algorithms.